Benzoxazole Copolymer

By copolymerizing 4-amino-3-hydroxybenzoic acid and 3,4-diaminobenzoic acid and cyclo-closing reaction, a benzoxazole-based copolymer with improved thermal stability and mechanical properties was prepared, which solved the shortcomings of the existing polybenzoxazole in terms of thermal stability and mechanical properties, and achieved significant improvement in the material.

JP7662575B2Active Publication Date: 2025-04-15KAO CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2022088803
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-05-31
Publication Date
2025-04-15
Estimated Expiration
2042-05-31

AI Technical Summary

Technical Problem

The existing monomers of polybenzoxazole have shortcomings in terms of thermal stability and mechanical properties, especially because their monomers are prone to become brittle at high temperatures and lack thermal stability.

Method used

By copolymerizing 4-amino-3-hydroxybenzoic acid and 3,4-diaminobenzoic acid and cyclo-closing reaction, a benzoxazole-based copolymer with improved thermal stability and mechanical properties was prepared.

Benefits of technology

The benzoxazole-based copolymer has achieved significant improvements in thermal stability and mechanical properties, with excellent thermal stability and film formation performance, while improving the mechanical properties of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007662575000019
    Figure 0007662575000019
  • Figure 0007662575000020
    Figure 0007662575000020
  • Figure 0007662575000021
    Figure 0007662575000021
Patent Text Reader

Abstract

To provide a benzoxazole-based copolymer that is superior in heat resistance and film formability, and has superior mechanical properties and a method for producing the same, and a film and a molding material each including the benzoxazole-based copolymer.SOLUTION: A benzoxazole-based copolymer includes a repeat unit represented by formula (I) (where R1 and R2 independently represent a hydrogen atom, an alkyl group, an alkoxy group, a hydroxy group, a carboxyl group, an amino group or a halogen atom) and a repeat unit with a specific benzimidazole structure.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a benzoxazole-based copolymer. More specifically, the present invention relates to a benzoxazole-based copolymer and a method for producing the same, as well as to a film and a molding material containing the benzoxazole-based copolymer. [Background technology]

[0002] Polybenzoxazole is used as an engineering plastic due to its excellent heat resistance, and is utilized as a fiber material and the like (see, for example, Non-Patent Document 1).

[0003] The benzoxazole skeleton of polybenzoxazole is produced by condensation of an o-aminophenol skeleton with a carboxylic acid, and therefore, the use of 4-amino-3-hydroxybenzoic acid having the o-aminophenol skeleton as a raw material monomer for polybenzoxazole has been investigated (for example, see Non-Patent Document 2).

[0004] In recent years, a method for producing 4-amino-3-benzoic acid from 4-aminobenzoic acid using a polypeptide having 4-aminobenzoic acid hydroxylation activity has been proposed (see, for example, Patent Documents 1 and 2). According to this method, 4-amino-3-hydroxybenzoic acid can be efficiently produced. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2021-101626 A [Patent Document 2] Patent Publication No. 2021-101627 [Non-patent literature]

[0006] [Non-Patent Document 1] Hirotaka Murase, SENI GAKKAISHI (Textiles and Industry), Vol. 66, No. 6, 2010 [Non-Patent Document 2] Lon J. Mathias et al., Macromolecules, Vol.18, No.4, pp.616-622 (1985) Summary of the Invention [Problem to be solved by the invention]

[0007] The use of 4-amino-3-hydroxybenzoic acid as a raw material monomer for polybenzoxazole has been considered. However, the homopolymer of polybenzoxazole has brittleness, so there is room for improvement in stress characteristics of the homopolymer of polybenzoxazole, and further improvement in heat resistance is desired.

[0008] The present invention has been made in view of the above-mentioned conventional techniques, and an object of the present invention is to provide a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties, a method for producing the same, and a film and molding material containing the benzoxazole-based copolymer. [Means for solving the problem]

[0009] The present invention relates to (1) Formula (I):

[0010] [ka]

[0011] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. and a repeating unit represented by formula (II):

[0012] [ka]

[0013] (In the formula, R 3 and R 4 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. A benzoxazole-based copolymer having a repeating unit represented by (2) A method for producing the benzoxazole-based copolymer according to (1) above, which comprises polymerizing a 4-amino-3-hydroxybenzoic acid compound with a 3,4-diaminobenzoic acid compound and then subjecting the resulting precursor of the benzoxazole-based copolymer to a ring-closing reaction; (3) A film containing the benzoxazole copolymer described in (1) above, and (4) A molding material containing the benzoxazole copolymer described in (1) above. Regarding. Effect of the Invention

[0014] According to the present invention, there are provided a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties, a method for producing the same, and a film and molding material containing the benzoxazole-based copolymer. [Brief description of the drawings]

[0015] [Figure 1] 1 is a graph showing the nuclear magnetic resonance (13C-NMR) spectrum of the benzoxazole-based copolymer obtained in Example 1. [Diagram 2] 1 is a graph showing the Fourier transform infrared spectroscopy (FT-IR) spectrum of the benzoxazole-based copolymer obtained in Example 1. [Diagram 3] 1 is a graph showing the nuclear magnetic resonance (13C-NMR) spectrum of the benzoxazole-based copolymer obtained in Example 2. [Figure 4]1 is a graph showing the Fourier transform infrared spectroscopy (FT-IR) spectrum of the benzoxazole-based copolymer obtained in Example 2. [Diagram 5] 1 is a graph showing the nuclear magnetic resonance (13C-NMR) spectrum of the benzoxazole-based copolymer obtained in Example 3. [Figure 6] 1 is a graph showing the Fourier transform infrared spectroscopy (FT-IR) spectrum of the benzoxazole-based copolymer obtained in Example 3. [Figure 7] 1 is a graph showing the nuclear magnetic resonance (13C-NMR) spectrum of the benzoxazole-based copolymer obtained in Example 4. [Figure 8] 1 is a graph showing the Fourier transform infrared spectroscopy (FT-IR) spectrum of the benzoxazole-based copolymer obtained in Example 4. [Figure 9] 1 is a graph showing the nuclear magnetic resonance (13C-NMR) spectrum of the benzoxazole-based copolymer obtained in Example 5. [Figure 10] 1 is a graph showing the Fourier transform infrared spectroscopy (FT-IR) spectrum of the benzoxazole-based copolymer obtained in Example 5. [Figure 11] 1 is a graph showing the nuclear magnetic resonance (13C-NMR) spectrum of the benzoxazole-based copolymer obtained in Example 6. [Figure 12] 1 is a graph showing the Fourier transform infrared spectroscopy (FT-IR) spectrum of the benzoxazole-based copolymer obtained in Example 6. [Figure 13] 1 is a graph showing the nuclear magnetic resonance (13C-NMR) spectrum of the 2,6-polybenzoxazole obtained in Comparative Example 1. [Figure 14] 1 is a graph showing a Fourier transform infrared spectroscopy (FT-IR) spectrum of the 2,6-polybenzoxazole obtained in Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The benzoxazole-based copolymer of the present invention has formula (I):

[0017] [ka]

[0018] (In the formula, R 1 and R 2 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. and a repeating unit represented by formula (II):

[0019] [ka]

[0020] (In the formula, R 3 and R 4 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. The repeating unit has the following structure:

[0021] In the repeating unit represented by formula (I), R 1 and R 2 are each independently a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. Suitable alkyl groups include, for example, alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, a propyl group, and a butyl group. Suitable alkoxy groups include, for example, alkoxy groups having 1 to 4 carbon atoms, such as a methoxy group, an ethoxy group, a propoxy group, and a butoxy group. Examples of halogen atoms include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. R 1 and R 2 Among these, from the viewpoint of obtaining a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties, a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and an alkoxy group having 1 to 4 carbon atoms are preferred, a hydrogen atom and an alkyl group having 1 to 4 carbon atoms are more preferred, and a hydrogen atom is even more preferred.

[0022] In the repeating unit represented by formula (II), R 3 and R 4 are each independently a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. Suitable alkyl groups include, for example, alkyl groups having 1 to 4 carbon atoms, such as a methyl group, an ethyl group, a propyl group, and a butyl group. Suitable alkoxy groups include, for example, alkoxy groups having 1 to 4 carbon atoms, such as a methoxy group, an ethoxy group, a propoxy group, and a butoxy group. Examples of halogen atoms include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. R 3 and R 4 Among these, from the viewpoint of obtaining a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties, a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and an alkoxy group having 1 to 4 carbon atoms are preferred, a hydrogen atom and an alkyl group having 1 to 4 carbon atoms are more preferred, and a hydrogen atom is even more preferred.

[0023] The molar ratio of the repeating unit represented by formula (I) to the repeating unit represented by formula (II) [repeating unit represented by formula (I) / repeating unit represented by formula (II)] is preferably 10 / 90 to 50 / 50, more preferably 15 / 85 to 45 / 55, and even more preferably 15 / 85 to 40 / 60, from the viewpoint of obtaining a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties.

[0024] The viscosity average molecular weight of the benzoxazole copolymer of the present invention is not particularly limited, but from the viewpoint of obtaining a benzoxazole copolymer having excellent heat resistance and film formability and good mechanical properties, it is preferably 15,000 to 800,000 g / mol, more preferably 20,000 to 500,000 g / mol, and even more preferably 50,000 to 200,000 g / mol. The viscosity average molecular weight of the benzoxazole copolymer is a value measured based on the method described in the following examples.

[0025] The benzoxazole copolymer of the present invention may contain other repeating units than the repeating units represented by formula (I) and the repeating units represented by formula (II) within the scope of the present invention. The other repeating units include repeating units inevitably produced as by-products when a 4-amino-3-hydroxybenzoic acid compound and a 3,4-diaminobenzoic acid compound are polymerized, as well as repeating units based on a third monomer other than a 4-amino-3-hydroxybenzoic acid compound and a 3,4-diaminobenzoic acid compound. The third monomer may be used within the scope of the present invention.

[0026] The benzoxazole copolymer of the present invention can be obtained, for example, by polymerizing a 4-amino-3-hydroxybenzoic acid compound and a 3,4-diaminobenzoic acid compound, and then carrying out a ring-closing reaction of the resulting benzoxazole copolymer precursor.

[0027] The 4-amino-3-hydroxybenzoic acid compound may, for example, be a compound represented by the formula (III):

[0028] [ka]

[0029] [In the formula, R 1 and R 2 is the same as above, and R 5 is an amino group or a group of the formula: -NH3 + X - (X represents a halogen atom). Examples of the 4-amino-3-hydroxybenzoic acid compound include the compound represented by the formula: 1 and R 2is the same as above, but from the viewpoint of obtaining a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties, a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and an alkoxy group having 1 to 4 carbon atoms are preferred, a hydrogen atom and an alkyl group having 1 to 4 carbon atoms are more preferred, and a hydrogen atom is even more preferred. X is a halogen atom. Examples of halogen atoms include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Of these halogen atoms, a chlorine atom is preferred.

[0030] In formula (III), R 1 and R 2 A 4-amino-3-hydroxybenzoic acid compound in which each of X is a hydrogen atom is 4-amino-3-hydroxybenzoic acid. 4-Amino-3-hydroxybenzoic acid can be efficiently prepared, for example, by the methods described in JP 2021-101626 A and JP 2021-101627 A. In formula (III), a 4-amino-3-hydroxybenzoic acid compound in which X is a halogen atom can be easily prepared by halogenating 4-amino-3-hydroxybenzoic acid by a conventional method.

[0031] The 3,4-diaminobenzoic acid compound may, for example, be a compound represented by the formula (IV):

[0032] [ka]

[0033] [In the formula, R 3 and R 4 is the same as above, and R 6 and R 7 are each independently an amino group or a group of the formula: -NH3 + X - (X represents a halogen atom). Examples of the 3,4-diaminobenzoic acid compound include those represented by the formula: R 3 and R 4is the same as above, but from the viewpoint of obtaining a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties, a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, and an alkoxy group having 1 to 4 carbon atoms are preferred, a hydrogen atom and an alkyl group having 1 to 4 carbon atoms are more preferred, and a hydrogen atom is even more preferred. + X - In the group represented by the formula: X is a halogen atom. Examples of halogen atoms include a fluorine atom, a chlorine atom, a bromine atom, and an iodine atom. Among these halogen atoms, a chlorine atom is preferred.

[0034] In formula (IV), R 3 and R 4 3,4-Diaminobenzoic acid, in which X is a hydrogen atom, is readily available commercially. 3,4-Diaminobenzoic acid compounds, in which X is a halogen atom in the formula (IV), can be readily prepared by halogenating 3,4-diaminobenzoic acid by a conventional method.

[0035] The molar ratio of the 4-amino-3-hydroxybenzoic acid compound to the 3,4-diaminobenzoic acid compound (4-amino-3-hydroxybenzoic acid compound / 3,4-diaminobenzoic acid compound) is preferably 10 / 90 to 50 / 50, more preferably 15 / 85 to 45 / 55, and even more preferably 15 / 85 to 40 / 60, from the viewpoint of obtaining a benzoxazole-based copolymer having excellent heat resistance and film formability and good mechanical properties.

[0036] In addition, compounds other than 4-amino-3-hydroxybenzoic acid compounds and 3,4-diaminobenzoic acid compounds may be used within the scope of the present invention. Examples of other compounds include aromatic diamine compounds such as phenylenediamine and xylylenediamine, but the present invention is not limited to these examples.

[0037] Examples of the polymerization method of 4-amino-3-hydroxybenzoic acid compound and 3,4-diaminobenzoic acid compound include bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc., but the present invention is not limited to these examples. Among these polymerization methods, from the viewpoint of efficiently preparing a benzoxazole-based copolymer with a small amount of impurities, the bulk polymerization and solution polymerization are preferred, and the bulk polymerization is more preferred.

[0038] The polymerization reaction of the 4-amino-3-hydroxybenzoic acid compound with the 3,4-diaminobenzoic acid compound can be carried out in the presence or absence of an organic solvent.

[0039] The organic solvent is preferably an organic solvent capable of dissolving 4-amino-3-hydroxybenzoic acid compounds and 3,4-diaminobenzoic acid compounds at the polymerization reaction temperature, and exhibiting poor solubility or insolubility in benzoxazole-based copolymers. Examples of the organic solvent include aliphatic alcohols having 1 to 4 carbon atoms, such as methanol, ethanol, propanol, and butanol, ketone compounds such as acetone and methyl ethyl ketone, ethyl acetate, tetrahydrofuran, dioxane, chloroform, dichloromethane, chlorobenzene, phenol, and cresol, but the present invention is not limited to these examples. These organic solvents may be used alone or in combination of two or more kinds. The amount of the organic solvent is not particularly limited as long as it is an amount that can efficiently polymerize the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound. Generally, however, the amount is preferably about 3 to 20 times (mass) and more preferably about 5 to 15 times (mass) the total amount (mass) of the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound.

[0040] When a 4-amino-3-hydroxybenzoic acid compound and a 3,4-diaminobenzoic acid compound are polymerized, a suitable amount of a heat stabilizer can be used. Examples of the heat stabilizer include phenylphosphonic acid (PPA), dimethyl phenylphosphonate, diethyl phenylphosphonate, and diphenylphosphonic acid, but the present invention is not limited to these examples.

[0041] The polymerization reaction temperature between the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound is not particularly limited, but from the viewpoint of increasing the reaction efficiency, it is preferably about 120 to 220° C. The polymerization reaction temperature may be constant or may be increased stepwise.

[0042] The polymerization reaction time between the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound cannot be generally determined because it varies depending on the polymerization reaction temperature, etc., but is usually about 10 to 40 hours. The atmosphere during the polymerization reaction between the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound is preferably an inert gas such as nitrogen gas or argon gas, from the viewpoint of not being affected by oxygen contained in the air.

[0043] As described above, the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound are polymerized to obtain a precursor of a benzoxazole copolymer. The fact that the precursor of a benzoxazole copolymer has been obtained can be confirmed by, for example, nuclear magnetic resonance spectroscopy, infrared spectroscopy, etc.

[0044] When the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound are polymerized, the ring-closing reaction of the precursor of the benzoxazole copolymer produced may proceed at the same time. Therefore, the polymerization reaction of the 4-amino-3-hydroxybenzoic acid compound and the 3,4-diaminobenzoic acid compound and the ring-closing reaction of the precursor of the benzoxazole copolymer produced can be carried out continuously.

[0045] The ring-closing reaction of the precursor of the benzoxazole-based copolymer produced means a reaction in which the repeating unit based on the 4-amino-3-hydroxybenzoic acid compound and the repeating unit based on the 3,4-diaminobenzoic acid compound are each ring-closed. The ring-closing reaction of the precursor of the benzoxazole-based copolymer can be carried out by maintaining the temperature of the precursor of the benzoxazole-based copolymer at a temperature of 200°C or higher. The temperature of the benzoxazole-based copolymer when the ring-closing reaction of the precursor of the benzoxazole-based copolymer is carried out is preferably 200°C or higher, more preferably 210°C or higher, and even more preferably 220°C or higher, from the viewpoint of efficiently carrying out the ring-closing reaction. The upper limit of the temperature of the benzoxazole-based copolymer when the ring-closing reaction of the precursor of the benzoxazole-based copolymer is not particularly limited, but is preferably 300°C or lower, more preferably 280°C or lower, and even more preferably 260°C or lower, from the viewpoint of suppressing the decomposition of the benzoxazole-based copolymer produced and increasing energy efficiency. The temperature of the benzoxazole-based copolymer during the ring-closing reaction of the precursor of the benzoxazole-based copolymer may be constant or may be varied.

[0046] When carrying out the ring-closing reaction of the precursor of the benzoxazole-based copolymer, a suitable amount of a heat stabilizer can be used. As the heat stabilizer, the same compounds as those mentioned above can be used.

[0047] The time required for the ring-closing reaction of the precursor of the benzoxazole-based copolymer cannot be generally determined because it varies depending on the heating temperature, etc., but is usually about 10 to 24 hours. The atmosphere in which the ring-closing reaction of the precursor of the benzoxazole-based copolymer is carried out is preferably an inert gas such as nitrogen gas or argon gas, from the viewpoint of not being affected by oxygen contained in the air.

[0048] The ring-closing reaction of the precursor of the benzoxazole copolymer as described above gives the benzoxazole copolymer of the present invention. The formation of the benzoxazole copolymer can be confirmed by, for example, nuclear magnetic resonance spectroscopy, infrared spectroscopy, etc.

[0049] The benzoxazole copolymer obtained above may be used as it is, or may be purified by washing with water or neutralized to remove impurities contained in the benzoxazole copolymer. The benzoxazole copolymer obtained above may be recovered by a method such as filtration. The recovered benzoxazole copolymer may be dried, for example, by drying under reduced pressure.

[0050] Since the benzoxazole copolymer of the present invention has the repeating unit represented by formula (I) and the repeating unit represented by formula (II), it has excellent heat resistance and film formability, and has good mechanical properties.

[0051] The benzoxazole-based copolymer is usually a random copolymer having a repeating unit represented by formula (I) and a repeating unit represented by formula (II), but the repeating unit represented by formula (I) and the repeating unit represented by formula (II) may be present alternately or in a block form.

[0052] The benzoxazole copolymer may contain an appropriate amount of additives depending on the application, if necessary. Examples of additives include colorants such as pigments and dyes, ultraviolet absorbers, ultraviolet stabilizers, antioxidants, rust inhibitors, antibacterial agents, plasticizers, algae inhibitors, mildew inhibitors, flame retardants, and foaming agents, but the present invention is not limited to these examples. These additives may be used alone or in combination of two or more types. The amount of additives varies depending on the type of additive, so it cannot be determined in general, and it is preferable to determine the amount appropriately depending on the type of additive.

[0053] Since the benzoxazole-based copolymer of the present invention is soluble in various organic solvents, it can be suitably used as a molding material for a molded article having a desired shape, a raw material for a film, etc. The molded article can be obtained, for example, by using a solution in which the benzoxazole-based copolymer is dissolved in an organic solvent as a molding material, and molding the molding material by a molding method such as blow molding, extrusion molding, or injection molding.

[0054] Examples of the organic solvent include trifluoroacetic acid, methylsulfonic acid, hexafluoroisopropanol, dimethylsulfoxide, dimethylacetamide, dichloromethane, etc., but the present invention is not limited to these examples. These organic solvents may be used alone or in combination of two or more kinds.

[0055] The amount of organic solvent relative to the benzoxazole-based copolymer of the present invention cannot be determined in general because it varies depending on the type of the organic solvent, the desired viscosity of the organic solvent solution of the benzoxazole-based copolymer, etc. Usually, it is preferable to mix the benzoxazole-based copolymer and the organic solvent in a desired ratio so that the organic solvent solution of the benzoxazole-based copolymer has a desired viscosity at a predetermined temperature.

[0056] The film made of the benzoxazole copolymer of the present invention can be obtained by forming an organic solvent solution of the benzoxazole copolymer into a film by a method such as casting or flow casting. After forming the film, the film may be dried to remove the organic solvent contained in the film. The thickness of the film formed varies depending on the application of the film and cannot be determined in general, but is usually about 3 to 800 μm. EXAMPLES

[0057] Next, the present invention will be described in more detail based on examples, but the present invention is not limited to these examples.

[0058] The structures and molecular weights of the polymers obtained in the following Examples and Comparative Examples were determined by the following methods.

[0059] (1) Nuclear magnetic resonance ( 13 C-NMR spectrum Polymer Nuclear Magnetic Resonance ( 13 C-NMR spectrum was measured using a nuclear magnetic resonance spectrometer (Bruker Avance III, 500 MHz, product name). 5 mg of sample (polymer) was packed into a zirconia rotor with a diameter of 7 mm and rotated at 8 kHz. The contact time and accumulation time were set to 2 seconds and 5 seconds, respectively, and the accumulation number was set to 15,000.

[0060] (2) Fourier transform infrared (FT-IR) spectrum The measurement device used was a Perkin Elmer Spectrum 100 (ATR method), and the measurement wavenumber range was 400 to 4000 cm -1 The Fourier transform infrared spectroscopy (FT-IR) was measured with the number of integrations set to 16.

[0061] [Viscosity average molecular weight of polymer] The viscosity average molecular weight of a polymer was determined based on the intrinsic viscosity of the polymer according to the following method.

[0062] A homogeneous solution was obtained by dissolving 100 mg of the polymer in 15 mL of 98% sulfuric acid. The relative viscosity of the obtained solution was measured at 25°C using an Ubbelohde viscometer. The time (t0) for sulfuric acid to pass through a specific length of the viscometer and the time (t) for the polymer solution to pass through the same specific length were measured, and the relative viscosity (η rel ) into equation (1): η rel =t / t0(1) It was calculated based on the above.

[0063] Next, the specific viscosity (η sp ) into equation (2): η sp =(t-t0) / t0=η rel -1 (2) Then, the intrinsic viscosity [η int (unit: dL / g) according to the Solomon-Ciuta formula (3):

[0064]

number

[0065] (wherein c represents the concentration of the polymer in the solution). For reference, the following references for Solomon-Ciuta's formula (3) are R. Pamies, JG Hernandez Cifre, M. del Carmen Lopez Martinez and J. Garcia de la Torre, Colloid Polym. Sci., 2008, 286, 1223-1231.

[0066] Next, the viscosity average molecular weight [M w (unit: g / mol)] according to the Mark-Houwink equation (4): η int =KM w a (4) (Wherein, K is 1.94 × 10 -4 , a indicates 0.791) For reference, the following references for Mark-Houwink's formula (4) are listed: J. Lobato, P. Canizares, MA Rodrigo, JJ Linares and JA Aguilar, J. Memb. Sci., 2007, 306, 47-55.

[0067] Polymer Properties (1) Heat resistance of polymers Using a thermogravimetric analyzer (Seiko Instruments Inc., product number: SSC / 5200SII), the polymer was subjected to thermogravimetric analysis in a temperature range of 25 to 800°C at a heating rate of 10°C / min in a nitrogen gas atmosphere. Based on the results of the thermogravimetric analysis, the 5% weight loss temperature (T d5 ) and 10% weight loss temperature (T d10 The 5% weight loss temperature means the temperature at which the mass of the sample (polymer) is reduced by 5%, and the 10% weight loss temperature means the temperature at which the mass of the sample (polymer) is reduced by 10%.

[0068] (2) Breaking stress, elongation at break, Young's modulus and toughness of the film A film having a width of 7 mm, a length of 40 mm, and a thickness of 15 μm was used, and the maximum strength (breaking stress) until the film broke was measured by pulling it at room temperature at a crosshead speed of 0.4 mm / sec using a tensile tester (Instron, product number: 3365-L5). The elongation at break of the film was determined by measuring the tensile strength of the film, determining the length by which the film stretched when it broke, dividing the elongated length by the original length of the film, and multiplying the result by 100. The Young's modulus of the film was determined from the initial slope of the stress-strain curve. The toughness of the film was determined as the integral area of ​​the region enclosed by the stress-strain curve.

[0069] [Polymer Solubility] 5 mg of polymer was added to 2 mL of each solvent, and left to stand at room temperature (approximately 20°C), and it was checked whether the polymer had dissolved in the solvent 1 hour after the start of the polymer addition. If the polymer had not dissolved in the solvent even after 1 hour from the start of the polymer addition, it was examined whether it would dissolve by irradiating it with ultrasonic waves or heating it to 60°C.

[0070] The evaluation criteria for solubility are as follows: [Evaluation Criteria] +: Polymer completely dissolved ±: Polymer partially dissolved -: Polymer is insoluble

[0071] Preparation Example 1 (Preparation of 4-amino-3-hydroxybenzoic acid hydrochloride) 6.0 g (39.2 mmol) of 4-amino-3-hydroxybenzoic acid was dispersed in 30 mL of methanol to obtain a dispersion. 12 N hydrochloric acid was added dropwise to the dispersion obtained above under stirring until 4-amino-3-hydroxybenzoic acid was completely dissolved, and after the color of the dispersion changed from pink to dark red, stirring was continued for another 4 hours at room temperature to obtain a yellow dispersion of 4-amino-3-hydroxybenzoic acid hydrochloride. The solvent was removed from the dispersion obtained above by evaporation to obtain 5.4 g of 4-amino-3-hydroxybenzoic acid hydrochloride (yield: 94%).

[0072] Preparation Example 2 (Preparation of 3,4-diaminobenzoic acid hydrochloride) 3,4-Diaminobenzoic acid hydrochloride was obtained in the same manner as in Preparation Example 1, except that 9.0 g (40.0 mg) of 3,4-diaminobenzoic acid hydrochloride was used instead of 4-amino-3-hydroxybenzoic acid.

[0073] Example 1 (Preparation of 2,6-benzoxazole-based copolymer)

[0074] [ka]

[0075] 25 g of polyphosphoric acid was placed in a three-necked round-bottom flask equipped with a magnetic stirrer, and the contents of the flask were heated at 100°C for 1 hour under a nitrogen gas atmosphere to remove traces of moisture. Then, 226.8 mg (1.20 mmol) of 4-amino-3-hydroxybenzoic acid and 1080.0 mg (4.80 mmol) of 3,4-diaminobenzoic acid hydrochloride were added to the flask, and the contents of the flask were continuously stirred for 1 hour to dissolve each compound.

[0076] The contents of the flask were then heated at 160°C for 4 hours, then at 180°C for 4 hours, then at 200°C for 4 hours, and then at 220°C for 12 hours, thereby successively carrying out the polymerization reaction of 4-amino-3-hydroxybenzoic acid with 3,4-diaminobenzoic acid hydrochloride and the ring-closing reaction of the resulting precursor of the 2,6-benzoxazole-based copolymer, and the color of the contents changed from red to dark brown.

[0077] The solution obtained above was dispersed in water, and the resulting dispersion was stirred for 12 hours. After that, polyphosphoric acid was removed from the dispersion, and the dispersion was filtered to obtain a brown solid.

[0078] The solid thus obtained was dried under reduced pressure, and then pulverized to obtain a powder. The powder thus obtained was suspended in deionized water, and 1 M aqueous sodium hydroxide solution was slowly added to the suspension, and the suspension was stirred for 1 hour until the pH of the suspension reached 7.0.

[0079] The solid was collected from the suspension by filtration and dried under reduced pressure to obtain 621.0 mg (5.4 mmol) of a brown powder of 2,6-benzoxazole-based copolymer (hereinafter referred to as PBOBI-A) (yield: 89%).

[0080] The nuclear magnetic resonance (NMR) of PBOBI-A obtained above ( 13 The C-NMR spectrum is shown in FIG. 1, and the Fourier transform infrared (FT-IR) spectrum is shown in FIG.

[0081] Example 2 (Preparation of 2,6-benzoxazole-based copolymer) In Example 1, the amount of 4-amino-3-hydroxybenzoic acid was changed to 113.4 mg (0.6 mmol), and the amount of 4-amino-3-hydroxybenzoic acid was changed to 1215 mg (5.4 mol), but the same procedure as in Example 1 was repeated to obtain a brown 2,6-benzoxazole-based copolymer (hereinafter referred to as PBOBI-B) powder.

[0082] The nuclear magnetic resonance of PBOBI-B obtained above ( 13 The C-NMR spectrum is shown in FIG. 3, and the Fourier transform infrared (FT-IR) spectrum is shown in FIG. 4.

[0083] Example 3 (Preparation of 2,6-benzoxazole-based copolymer) In Example 1, the amount of 4-amino-3-hydroxybenzoic acid was changed to 340.2 mg (1.8 mmol), and the amount of 3,4-diaminobenzoic acid hydrochloride was changed to 945 mg (4.2 mmol), but the same procedure as in Example 1 was repeated to obtain a brown benzoxazole-based copolymer (hereinafter referred to as PBOBI-C) powder.

[0084] The nuclear magnetic resonance (NMR) of PBOBI-C obtained above ( 13 The C-NMR spectrum is shown in FIG. 5, and the Fourier transform infrared spectroscopy (FT-IR) spectrum is shown in FIG. 6.

[0085] Example 4 (Preparation of 2,6-benzoxazole-based copolymer) In Example 1, the amount of 4-amino-3-hydroxybenzoic acid was changed to 453.6 mg (2.4 mmol), and the amount of 3,4-diaminobenzoic acid hydrochloride was changed to 810 mg (3.6 mmol), but the same procedure as in Example 1 was repeated to obtain a brown benzoxazole-based copolymer (hereinafter referred to as PBOBI-D) powder.

[0086] The nuclear magnetic resonance (NMR) of PBOBI-D obtained above ( 13 The C-NMR spectrum is shown in FIG. 7, and the Fourier transform infrared (FT-IR) spectrum is shown in FIG.

[0087] Example 5 (Preparation of 2,6-benzoxazole-based copolymer) In Example 1, the amount of 4-amino-3-hydroxybenzoic acid was changed to 567.0 mg (3.0 mmol), and the amount of 3,4-diaminobenzoic acid hydrochloride was changed to 675 mg (3.0 mmol), but the same procedure as in Example 1 was repeated to obtain a brown 2,6-benzoxazole-based copolymer (hereinafter referred to as PBOBI-E) powder.

[0088] The nuclear magnetic resonance (NMR) of PBOBI-E obtained above ( 13 The C-NMR spectrum is shown in FIG. 9, and the Fourier transform infrared (FT-IR) spectrum is shown in FIG.

[0089] Example 6 (Preparation of 2,6-benzoxazole-based copolymer) In Example 1, the amount of 4-amino-3-hydroxybenzoic acid was changed to 680.4 mg (3.6 mmol), and the amount of 3,4-diaminobenzoic acid hydrochloride was changed to 540 mg (2.4 mmol), but the same procedure as in Example 1 was repeated to obtain a brown 2,6-benzoxazole-based copolymer (hereinafter referred to as PBOBI-F) powder.

[0090] The nuclear magnetic resonance (NMR) of PBOBI-F obtained above ( 13 The C-NMR spectrum is shown in FIG. 11, and the Fourier transform infrared spectroscopy (FT-IR) spectrum is shown in FIG.

[0091] Comparative Example 1 (Preparation of 2,6-polybenzoxazole)

[0092] [ka]

[0093] 25 g of polyphosphoric acid was placed in a three-necked round-bottom flask equipped with a magnetic stirrer, and the contents of the flask were heated at 100°C for 1 hour under a nitrogen gas atmosphere to remove traces of moisture. Then, 1134 mg (6 mmol) of 4-amino-3-hydroxybenzoic acid hydrochloride was added to the flask, and the contents of the flask were continuously stirred for 1 hour to dissolve each compound.

[0094] The contents of the flask were then heated at 160° C. for 4 hours, then 180° C. for 4 hours, then 200° C. for 4 hours, followed by heating at 220° C. for 12 hours.

[0095] The content of the flask heated as described above was dispersed in water, and the resulting dispersion was stirred for 12 hours. After that, polyphosphoric acid was removed from the dispersion, and the dispersion was filtered to obtain a solid.

[0096] The solid thus obtained was dried under reduced pressure, and then pulverized to obtain a powder. The powder thus obtained was suspended in deionized water, and 1 M aqueous sodium hydroxide solution was slowly added to the suspension, and the suspension was stirred for 1 hour until the pH of the suspension reached 7.0.

[0097] The solid was collected from the suspension by filtration and dried under reduced pressure to obtain 2,6-polybenzoxazole (hereinafter referred to as PBO-A).

[0098] The nuclear magnetic resonance of PBO-A obtained above ( 13 The C-NMR spectrum is shown in FIG. 13, and the Fourier transform infrared spectroscopy (FT-IR) spectrum is shown in FIG.

[0099] Comparative Example 2 (Preparation of 2,5-polybenzoxazole)

[0100] [ka]

[0101] 25 g of polyphosphoric acid was placed in a three-necked round-bottom flask equipped with a magnetic stirrer, and the contents of the flask were heated at 100°C for 1 hour under a nitrogen gas atmosphere to remove traces of moisture. Then, 1134 mg (6 mmol) of 3-amino-4-hydroxybenzoic acid hydrochloride was added to the flask, and the contents of the flask were continuously stirred for 1 hour to dissolve each compound.

[0102] The contents of the flask were then heated at 160° C. for 4 hours, then 180° C. for 4 hours, then 200° C. for 4 hours, followed by heating at 220° C. for 12 hours.

[0103] The content of the flask heated as described above was dispersed in water, and the resulting dispersion was stirred for 12 hours. After that, polyphosphoric acid was removed from the dispersion, and the dispersion was filtered to obtain a solid.

[0104] The solid thus obtained was dried under reduced pressure, and then pulverized to obtain a powder. The powder thus obtained was suspended in deionized water, and 1 M aqueous sodium hydroxide solution was slowly added to the suspension, and the suspension was stirred for 1 hour until the pH of the suspension reached 7.0.

[0105] The solid was collected from the suspension by filtration and dried under reduced pressure to obtain 2,5-polybenzoxazole (hereinafter referred to as PBO-B).

[0106] The fact that PBO-B was obtained in Comparative Example 2 is 13 The results were confirmed by C-NMR and infrared absorption spectroscopy.

[0107] Comparative Example 3 (Preparation of Benzoxazole Copolymer)

[0108] [ka]

[0109] 25 g of polyphosphoric acid was placed in a three-necked round-bottom flask equipped with a magnetic stirrer, and the contents of the flask were heated at 100° C. for 1 hour under a nitrogen gas atmosphere to remove traces of moisture. Subsequently, 567.0 mg (3.0 mmol) of 4-amino-3-hydroxybenzoic acid hydrochloride and 567.0 mg (3.0 mmol) of 3-amino-4-hydroxybenzoic acid hydrochloride were added to the flask, and the contents of the flask were continuously stirred for 1 hour to dissolve each compound.

[0110] The contents of the flask were then heated at 160°C for 4 hours, then at 180°C for 4 hours, then at 200°C for 4 hours, and subsequently at 220°C for 12 hours, thereby successively carrying out the polymerization reaction of 4-amino-3-hydroxybenzoic acid with 3-amino-4-hydroxybenzoic acid hydrochloride and the ring-closure reaction of the resulting precursor of 2,6-polybenzoxazole.

[0111] The content of the flask heated as described above was dispersed in water, and the resulting dispersion was stirred for 12 hours. After that, polyphosphoric acid was removed from the dispersion, and the dispersion was filtered to obtain a solid.

[0112] The solid thus obtained was dried under reduced pressure, and then pulverized to obtain a powder. The powder thus obtained was suspended in deionized water, and 1 M aqueous sodium hydroxide solution was slowly added to the suspension, and the suspension was stirred for 1 hour until the pH of the suspension reached 7.0.

[0113] The solid was collected from the suspension by filtration and dried under reduced pressure to obtain 2,6-polybenzoxazole (hereinafter referred to as PBOBO).

[0114] The fact that PBOBO was obtained in Comparative Example 3 is 13 The results were confirmed by C-NMR and infrared absorption spectroscopy.

[0115] Comparative Example 4 (Preparation of 2,5-benzoxazole-based copolymer)

[0116] [ka]

[0117] 25 g of polyphosphoric acid was placed in a three-necked round-bottom flask equipped with a magnetic stirrer, and the contents of the flask were heated at 100°C for 1 hour under a nitrogen gas atmosphere to remove traces of moisture. Then, 226.8 mg (1.20 mmol) of 3-amino-4-hydroxybenzoic acid and 1080.0 mg (4.80 mmol) of 3,4-diaminobenzoic acid hydrochloride were added to the flask, and the contents of the flask were continuously stirred for 1 hour to dissolve each compound.

[0118] The contents of the flask were then heated at 160°C for 4 hours, then at 180°C for 4 hours, then at 200°C for 4 hours, and then at 220°C for 12 hours, thereby successively carrying out the polymerization reaction of 3-amino-4-hydroxybenzoic acid with 3,4-diaminobenzoic acid hydrochloride and the ring-closing reaction of the resulting precursor of the 2,5-benzoxazole-based copolymer, and the color of the contents changed from red to dark brown.

[0119] The solution obtained above was dispersed in water, and the resulting dispersion was stirred for 12 hours. After that, polyphosphoric acid was removed from the dispersion, and the dispersion was filtered to obtain a brown solid.

[0120] The solid thus obtained was dried under reduced pressure, and then pulverized to obtain a powder. The powder thus obtained was suspended in deionized water, and 1 M aqueous sodium hydroxide solution was slowly added to the suspension, and the suspension was stirred for 1 hour until the pH of the suspension reached 7.0.

[0121] The solid was collected from the suspension by filtration and dried under reduced pressure to obtain 621.0 mg (5.4 mmol) of a brown powder of 2,5-benzoxazole-based copolymer (hereinafter referred to as PBOBI-G) (yield: 89%).

[0122] The fact that PBOBI-G was obtained in Comparative Example 4 is 13 The results were confirmed by C-NMR and infrared absorption spectroscopy.

[0123] Comparative Example 5 (Preparation of 2,5-benzoxazole-based copolymer) In Comparative Example 4, the amount of 3-amino-4-hydroxybenzoic acid was changed to 453.6 mg (2.4 mmol), and the amount of 3,4-diaminobenzoic acid hydrochloride was changed to 810 mg (3.6 mmol), but the same procedure as in Comparative Example 4 was repeated to obtain a brown 2,5-benzoxazole-based copolymer (hereinafter referred to as PBOBI-H) powder.

[0124] The nuclear magnetic resonance of PBOBI-H obtained above ( 13 The C-NMR spectrum and infrared absorption spectrum of PBOBI-G obtained in Comparative Example 4 were both determined by the nuclear magnetic resonance ( 13 The C-NMR spectrum and infrared absorption spectrum were similar.

[0125] Comparative Example 6 (Preparation of 2,5-benzoxazole-based copolymer) In Comparative Example 4, the amount of 3-amino-4-hydroxybenzoic acid was changed to 945.0 mg (5.0 mmol), and the amount of 3,4-diaminobenzoic acid hydrochloride was changed to 1125 mg (5.0 mmol), but the same procedure as in Comparative Example 4 was repeated to obtain a brown 2,5-benzoxazole-based copolymer (hereinafter referred to as PBOBI-I) powder.

[0126] The nuclear magnetic resonance (NMR) of PBOBI-I obtained above ( 13 The C-NMR spectrum and infrared absorption spectrum of PBOBI-G obtained in Comparative Example 4 were both determined by the nuclear magnetic resonance ( 13 The C-NMR spectrum and infrared absorption spectrum were similar.

[0127] Comparative Example 7 (Preparation of 2,5-Benzoxazole-Based Copolymer J) In Comparative Example 4, the amount of 3-amino-4-hydroxybenzoic acid was changed to 680.4 mg (3.6 mmol), and the amount of 3,4-diaminobenzoic acid hydrochloride was changed to 540 mg (2.4 mmol), but the same procedure as in Comparative Example 4 was repeated to obtain a brown 2,5-benzoxazole-based copolymer (hereinafter referred to as PBOBI-J) powder.

[0128] The nuclear magnetic resonance (NMR) of PBOBI-J obtained above ( 13 The C-NMR spectrum and infrared absorption spectrum of PBOBI-G obtained in Comparative Example 4 were both determined by the nuclear magnetic resonance ( 13 The C-NMR spectrum and infrared absorption spectrum were similar.

[0129] [Molecular weight of each polymer] The data regarding the molecular weight of each polymer obtained above is shown in Table 1 below.

[0130] [Table 1]

[0131] [Film Preparation] Each of the polymers obtained above was taken in an amount of 100 mg, and each polymer was dispersed in a mixed solvent of 3 mL of trifluoroacetic acid and 0.19 mL of methanesulfonic acid. The dispersion obtained above was stirred at 60° C. for 24 hours to dissolve the polymer and obtain a dark brown solution. The solution obtained above was taken with a dropper, uniformly applied onto a silicon plate, and dried at room temperature for 12 hours to evaporate the solvent, forming a film.

[0132] Next, the film obtained above was immersed in water at 25° C. for 12 hours to remove methanesulfonic acid contained in the film. Thereafter, the film was taken out of the water, sandwiched between two silicon plates, and dried under reduced pressure for 12 hours to obtain a film with a thickness of about 30 μm.

[0133] When films were produced in the same manner as described above using PBOBI-A to PBOBI-J as the benzoxazole-based copolymer, it was found that the durability of the film decreased as the content of 4-amino-3-hydroxybenzoic acid in the benzoxazole-based copolymer increased.

[0134] It was confirmed that when the content of 4-amino-3-hydroxybenzoic acid in the benzoxazole copolymer is 20 mol % or less, the film becomes flexible. Also, it was confirmed that when the content of 4-amino-3-hydroxybenzoic acid in the benzoxazole copolymer is 50 mol % or more, the film becomes brittle. From these, it was confirmed that the molar ratio of the repeating unit represented by formula (I) to the repeating unit represented by formula (II) [repeating unit represented by formula (I) / repeating unit represented by formula (II)] is preferably 20 / 80 to 50 / 50.

[0135] On the other hand, when a film was prepared in the same manner as described above using 100 mg of the PBO-A obtained in Comparative Example 1, the film was broken into powder when an attempt was made to peel it off from the silicon plate, indicating that the film was very brittle and that the mechanical properties of the film could not be measured.

[0136] In addition, films were prepared in the same manner as described above using 100 mg of PBO-B obtained in Comparative Example 2 or 100 mg of PBOBO obtained in Comparative Example 3. However, when an attempt was made to peel the resulting films off the silicon plate, they were easily destroyed, and the mechanical properties of these films could not be measured.

[0137] [Heat resistance of polymer] The 5% weight loss temperature and the 10% weight loss temperature were used as indicators of heat resistance. The measurement results of the 5% weight loss temperature and the 10% weight loss temperature of PBOBI-A to PBOBI-J, PBO-A, PBO-B and PBOBO are shown in Table 2.

[0138] [Table 2]

[0139] From the results shown in Table 2, it can be seen that the 5% weight loss temperatures and 10% weight loss temperatures of PBO-A to PBO-F obtained in each of the Examples are superior to those of PBOBI-G to PBOBI-J obtained in each of the Comparative Examples.

[0140] [Film breaking stress, elongation at break, Young's modulus and toughness] The mechanical properties of PBOBI-A, PBOBI-B, PBOBI-D, PBO-A, PBO-B, PBOBO, PBOBI-G and PBOBI-I were investigated in terms of film breaking stress, elongation at break, Young's modulus and toughness. The results are shown in Table 3.

[0141] [Table 3]

[0142] From the results shown in Table 3, it can be seen that the benzoxazole-based copolymers obtained in each Example are remarkably superior in breaking stress, elongation at break, rigidity (Young's modulus) and toughness compared with the PBO-A, PBO-B and PBOBO obtained in each Comparative Example, and that the breaking stress, elongation at break, rigidity and toughness improve as the content of the repeating unit represented by formula (II) in the benzoxazole-based copolymer increases.

[0143] [Polymer Solubility] The solubility of PBOBI-A to PBOBI-J, PBO-A, PBO-B and PBOBO obtained in each Example was examined. The results are shown in Table 4.

[0144] [Table 4]

[0145] From the results shown in Table 4, it can be seen that the benzoxazole copolymers obtained in each Example are all easily soluble in various solvents, which indicates that the solutions in which the benzoxazole copolymers obtained in each Example are dissolved in a solvent can be used as molding materials, and that the solutions can be made into films by a method such as casting to produce films. [Industrial Applicability]

[0146] The benzoxazole-based copolymer of the present invention is excellent in heat resistance and film formability and has good mechanical properties, and is therefore expected to be used as molding materials for electronic parts, electronic information materials, aerospace materials, etc., which require heat resistance, molding materials for various films, enamels for electric wires used in high-performance motors, etc. In addition, the benzoxazole-based copolymer of the present invention is not only excellent in heat resistance and film formability but also has good mechanical properties, and is therefore expected to be used in various applications, such as materials for disposable diapers and cosmetic sheets such as lotion wipes.

Claims

1. Formula (I): 【Chemistry 1】 (In the formula, R 1 and R 2 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. and a repeating unit represented by formula (II): 【Chemistry 2】 (In the formula, R 3 and R 4 each independently represents a hydrogen atom, an alkyl group, an alkoxy group, a hydroxyl group, a carboxyl group, an amino group, or a halogen atom. A benzoxazole-based copolymer having a repeating unit represented by the formula:

2. 2. The benzoxazole copolymer according to claim 1, wherein the molar ratio of the repeating unit represented by formula (I) to the repeating unit represented by formula (II) [repeating unit represented by formula (I) / repeating unit represented by formula (II)] is from 10 / 90 to 50 / 50.

3. 3. The process for producing a benzoxazole copolymer according to claim 1, which comprises polymerizing 4-amino-3-hydroxybenzoic acid and 3,4-diaminobenzoic acid, and then subjecting the resulting precursor of the benzoxazole copolymer to a ring-closing reaction.

4. A film comprising the benzoxazole copolymer according to claim 1 or 2.

5. A molding material comprising the benzoxazole copolymer according to claim 1 or 2.

Citation Information

Patent Citations

  • Synthesis of aromatic-heterocyclic polymer from precursor produced by biosynthesis

    JP1995309946A

  • Melting method of dead-soft steel with extra-low sulfur content

    JP1995316637A

  • polybenzazole block copolymer

    JP2008519877A

  • Polybenzazole and polybenzazole precursors

    JP2010525183A

  • Polypeptide having 4-aminobenzoic acid hydroxylation activity and use thereof

    JP2021101626A